Women in the mission of the church : their opportunities and obstacles throughout Christian history - Dzubinski, Leanne M., 1963-; Stasson, Anneke H. (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2021)
"Demonstrates the integral participation of women in the church's mission from the first century to the twentieth century, showing how they have overcome obstacles to their ministry and have transformed cultural constraints to spread the gospel"--
Includes bibliographical references (pages 215-232) and index.
Keywords: Women in Christianity -- History; Women in church work -- History; Mission of the church -- History